Hair care composition
Patent Information
- Application Number
- JP2020528137
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-01-17
- Filing Date
- 2018-11-14
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2038-11-14
Smart Images

Figure 0007636175000019 
Figure 0007636175000020 
Figure 0007636175000021
Abstract
Description
[Technical field]
[0001] The present invention relates to hair care compositions, particularly hair care compositions comprising a copolymer, certain anionic surfactants and a zinc-based anti-dandruff agent, which compositions provide smaller aggregate size, improved anti-dandruff agent delivery efficiency to the hair and / or scalp, and maximized anti-microbial efficacy. [Background technology]
[0002] Hair care compositions generally provide cleansing or conditioning benefits, or a combination of the two. Such compositions typically include one or more cleansing surfactants that generally aid in cleaning the hair and scalp free of undesirable dirt, particles, and fatty materials. Conditioning benefits are achieved by including one or more conditioning agents in the hair care composition. Conditioning benefits are achieved by the oily materials deposited on the hair forming a film that makes the hair easier to comb when wet and easier to manage when dry.
[0003] Additionally, anti-dandruff benefits have been provided through hair care compositions. Dandruff is a problem that affects many people worldwide. The condition is manifested by the shedding of clumps of dead skin cells from the scalp. These are white in color and provide an aesthetically unpleasant appearance. The causative agent of dandruff are certain members of the Malassezia yeasts. To combat these, anti-dandruff products have included certain anti-dandruff agents that have anti-fungal activity. Such products need to function as hair cleansing shampoos while reducing the causes of dandruff. Thus, there is a constant desire to improve the delivery efficiency of anti-dandruff agents to maximize the effectiveness of such anti-dandruff agents.
[0004] Typical antidandruff agents used in hair care are metal pyrithione salts such as zinc pyrithione, piroctone olamine (octopirox), azole-based antifungals (e.g. climbazole), selenium sulfide, and combinations thereof. Of these, zinc pyrithione is a particulate material.
[0005] Cationic polymers are often used to enhance deposition of conditioning and / or antidandruff agents to the hair and / or scalp. These polymers may be synthetic or natural polymers modified with cationic substituents.
[0006] However, it is well accepted that cationic polymers and anionic surfactants form polymer-surfactant complexes (flocculation) in shampoo systems, aiding in the deposition of anti-dandruff agents. The flocculation profile affects the delivery efficiency of anti-dandruff agents to the scalp and their distribution on the scalp. Clinical trials have demonstrated that large aggregate size is undesirable for anti-dandruff efficacy, as anti-dandruff agents are trapped in large aggregate particles and are difficult to release. The degree of substitution (DS) and molecular weight (MW) of the cationic polymer have been found to play an important role in the flocculation profile of anti-dandruff shampoos. For example, a higher DS promotes better deposition of anti-dandruff agents, but results in a faster flocculation rate, resulting in the formation of larger aggregate particles. Summary of the Invention [Problem to be solved by the invention]
[0007] The present inventors have recognized the need to develop a hair care composition that can provide a satisfactory aggregation profile while maintaining good deposition of antidandruff agents.Unexpectedly, it has been found that this need can be met by using a combination of a copolymer and an ethoxylated anionic surfactant having a specific degree of ethoxylation in a hair care composition.
[0008] Additional Information WO 2016 / 100466 discloses a hair care composition comprising: i) at least one crosslinked nonionic amphiphilic suspension polymer; ii) at least one anionic surfactant; iii) at least one particulate anti-dandruff agent; and iv) water. The suspension polymer is a pH-independent nonionic amphiphilic emulsion polymer that is crosslinked with an amphiphilic crosslinker and that effectively suspends the water-insoluble particulate anti-dandruff agent.
[0009] The above additional information does not describe a hair care composition comprising a copolymer containing specific cationic vinyl monomer units and specific vinyl monomer units in a specific ratio, an ethoxylated anionic surfactant with a specific degree of ethoxylation, and a zinc-based anti-dandruff agent, particularly one that can provide a satisfactory flocculation profile while maintaining good deposition of the anti-dandruff agent.
[0010] Tests and Definitions Hair care composition "Hair care composition" as used herein is meant to include compositions for topical application to mammalian, particularly human, hair and / or scalp. Such compositions are generally classified as leave-on or rinse-off and include any product applied to the human body to improve appearance, cleansing, odor control or general aesthetics. The compositions of the present invention may be in the form of a liquid, lotion, cream, foam, scrub, gel or bar. Non-limiting examples of such compositions include leave-on hair lotions, creams and rinse-off shampoos, conditioners, shower gels or toilet bars. The compositions of the present invention are preferably rinse-off compositions, particularly preferably shampoos or conditioners, and most preferably shampoos.
[0011] Delivery Efficiency "Delivery efficiency" as used herein refers to the ability to deliver and deposit an anti-dandruff agent onto the scalp surface of an individual.
[0012] Cation Charge Density As used herein, "cationic charge density" refers to the number of cationic charges per unit weight of a given polymer. The cationic charge density can be calculated from the degree of substitution as described in WO 2013 / 011122, the entire disclosure of which is incorporated herein by reference, particularly page 8, lines 8-17. For example, for a cationically modified guar polymer obtained by reacting with 2,3-epoxypropyltrimethylammonium chloride, the cationic charge density can be calculated from DS using the following formula:
number
[0013] Ethoxylation Degree As used herein, "degree of ethoxylation" refers to the average number of moles of ethylene oxide units per mole of ethoxylated product. The degree of ethoxylation is determined by the average number of moles of deuterium oxide (D 2 O) in a solvent 1 The degree of ethoxylation of sodium laureth sulfate (SLES) is measured using H NMR. 1 H NMR (Bruker-Biospin, 400 MHz) is used for the measurements, and the spectra are recorded at 25° C. Samples for measurements using NMR are prepared as follows: the samples are placed in a centrifuge tube and cooled to 37° C. 2 After dispersing in O and sonicating, the solution is filtered and transferred to an NMR tube. Peaks corresponding to the protons of the sample appear at approximately 3.98 ppm, approximately 4.15 ppm, and approximately 3.58 to 3.84 ppm. -CH appears at approximately 4.15 ppm and approximately 3.98 ppm. 2 The peak corresponding to the - proton is integrated as A1. 2 CH 2 The peaks corresponding to the four protons of - (appearing at 4.15 ppm, about 3.58 to about 3.84 ppm) are also integrated as A2. The degree of ethoxylation of SLES can be calculated as follows.
number
[0014] Average particle size "Average particle size" as used herein refers to the volume average particle size measured using light scattering techniques on a Malvern Mastersizer 2000 instrument. The settings used for the measurements included a particle absorption of 0.1, water as the dispersant, a 10-12% obscuration limit, and a pump speed of 960 rpm. The average particle size of a sample was determined from the particle size distribution curve as the average of three sample measurements.
[0015] water insoluble As used herein, "water-insoluble" refers to a solubility of a material in water of 0.1% by weight or less at 25° C. and atmospheric pressure.
[0016] molecular weight As used herein, "molecular weight" refers to the weight average molecular weight of a given polymer. The weight average molecular weight of a copolymer can be measured by gel permeation chromatography (e.g., using water / methanol / acetic acid / sodium acetate as the developing solvent).
[0017] others Except in the examples or where otherwise noted, all numbers in this description expressing amounts of ingredients or reaction conditions, physical properties of ingredients and / or uses can be understood to be modified by the word "about."
[0018] Unless otherwise stated, all amounts are by weight of the final oral care composition. It should be noted that when specifying a range of values, a particular upper value can be associated with a particular lower value.
[0019] For the avoidance of doubt, the word "comprising" is intended to mean "including" but not necessarily "consisting of" or "composed of." In other words, the listed steps or options need not be inclusive.
[0020] The disclosure of the invention found in this specification should be considered to cover all of the embodiments found in the claims as being multiple dependent on each other, regardless of the fact that the claims may be found without multiple dependency or redundancy.
[0021] Where features are disclosed with respect to particular embodiments of the invention (e.g., compositions of the invention), such disclosure should be deemed to apply mutatis mutandis to other embodiments of the invention (e.g., methods of the invention).
[0022] Summary of the Invention In a first aspect, the present invention provides a method for producing a medicament for the treatment of a cancer, comprising: a) copolymers; b) Formula: [ka] where R is an alkyl or alkenyl having 8 to 18 carbon atoms; M is a solubilizing cation including sodium, potassium, ammonium or mixtures thereof; and the degree of ethoxylation n is 2. an ethoxylated alkyl sulfate anionic surfactant having the formula: c) 0.01 to 5% by weight of a zinc-based anti-dandruff agent The present invention relates to a hair care composition comprising The copolymer may be: (i) Formula (1): [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, and R 2 ~R 4 Each of the following is independently1-24 Alkyl groups, preferably C 1-3 is an alkyl group, and X - are independently a fluoride, chloride, bromide or iodide anion, preferably chloride, and d is an integer from 1 to 10. A cationic vinyl monomer A represented by: (ii) Formula (2): [ka] (In the formula, R 5 is a hydrogen atom or a methyl group, and R 6 ~R 8 Each of the following is independently 1-24 Alkyl groups, preferably C 1-3 is an alkyl group, Y - are independently a fluoride, chloride, bromide or iodide anion, preferably chloride, and e is an integer from 1 to 10. a cationic vinyl monomer B represented by (iii) Formula (3): [ka] (In the formula, R 9 is a hydrogen atom or a methyl group, and R 10 and R 11 each independently represents a hydrogen atom or C 1-4 is an alkyl group, where R 10 and R 11 The total number of carbon atoms is 1 to 4. Vinyl monomer C represented by Including, The content of monomer A is 1-44 mol % based on the total monomer content of the copolymer, the content of monomer B is 1-44 mol %, and the content of monomer C is 20-75 mol % based on the total monomer content of the copolymer.
[0023] In a second aspect, the present invention relates to a packaged hair care product comprising the hair care composition of the first aspect of the present invention.
[0024] In a third aspect, the present invention relates to a method of depositing an anti-dandruff agent on the scalp comprising the step of applying a hair care composition of any embodiment of the first aspect of the present invention to a scalp surface of an individual.
[0025] All other aspects of the present invention will become more readily apparent in light of the following detailed description and examples. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 shows a graph of aggregate particle size distribution for samples containing different cationic polymers. [Diagram 2] FIG. 2 shows microscopic images of samples containing anionic surfactants with different degrees of ethoxylation at 10x magnification. [Diagram 3] FIG. 3 shows aggregate particle size distribution graphs for samples containing anionic surfactants with different degrees of ethoxylation.
[0027] Detailed Description It has been found that hair care compositions comprising a combination of a copolymer and an ethoxylated anionic surfactant having a particular degree of ethoxylation can provide a satisfactory flocculation profile while maintaining good deposition of anti-dandruff agents.
[0028] Copolymers suitable for use in the compositions of the present invention contain building blocks of cationic vinyl monomers A and B, as well as building blocks of vinyl monomer C.
[0029] The cationic vinyl monomer A has the formula (1): [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, and R 2 ~R 4 Each of the following is independently 1-24 Alkyl groups, preferably C 1-3 is an alkyl group, and X -are independently a fluoride, chloride, bromide or iodide anion, preferably chloride, and d is an integer from 1 to 10. It is represented by:
[0030] R 1 is preferably a hydrogen group. 2 ~R 4 is preferably a methyl group or an ethyl group, more preferably a methyl group; d is preferably an integer of 1 to 5, more preferably 3.
[0031] The cationic vinyl monomer A of formula (1) may be a (meth)acrylamide having a cationic group (wherein "(meth)acryl" represents acryl and methacryl). Illustrative but non-limiting examples of cationic vinyl monomer A that may be used in the present invention include, for example, N-(meth)acryloylaminopropyl-N,N,N-trimethylammonium chloride, N-(meth)acryloylaminopropyl-N,N-diethyl-N-methylammonium chloride, or a mixture thereof. Preferably, the cationic vinyl monomer A is N-(meth)acryloylaminopropyl-N,N,N-trimethylammonium chloride, more preferably acryloylaminopropyl-N,N,N-trimethylammonium chloride (propyltrimonium chloride acrylamide).
[0032] The cationic vinyl monomer B has the formula (2): [ka] (In the formula, R 5 is a hydrogen atom or a methyl group, and R 6 ~R 8 Each of the following is independently 1-24 Alkyl groups, preferably C 1-3 is an alkyl group, Y - are independently a fluoride, chloride, bromide or iodide anion, preferably chloride, and e is an integer from 1 to 10. It is represented by:
[0033] R 5 is preferably a methyl group. 6 ~R 8 is preferably a methyl group or an ethyl group, more preferably a methyl group; and e is an integer of 1 to 5.
[0034] The cationic vinyl monomer B of formula (2) may be a (meth)acrylic acid ester having a cationic group (wherein "(meth)acrylic" stands for acrylic and methacrylic). Preferably, the cationic vinyl monomer B is N-(meth)acryloyloxyethyl-N,N,N-trimethylammonium chloride, more preferably N-methacryloyloxyethyl-N,N,N-trimethylammonium chloride (ethyltrimonium chloride methacrylate).
[0035] The content of monomer A is 1-44 mol%, preferably 3-40 mol%, more preferably 5-40 mol%, most preferably 10-30 mol%, based on the total monomer content of the copolymer. The content of monomer B is 1-44 mol%, preferably 3-40 mol%, more preferably 5-40 mol%, most preferably 10-30 mol%, based on the total monomer content of the copolymer. The total content of the two cationic vinyl monomers A and B is preferably 25-45 mol%, more preferably 30-40 mol%, based on the total monomer content of the copolymer.
[0036] The vinyl monomer C has the formula (3): [ka] (In the formula, R 9 is a hydrogen atom or a methyl group, and R 10 and R 11 each independently represents a hydrogen atom or C 1-4 is an alkyl group, where R 10 and R 11 The total number of carbon atoms is 1 to 4. It is represented by:
[0037] R 9 is preferably a hydrogen atom. 6 ~R 8 are hydrogen atoms or C 1-3 It is an alkyl group. 1-3 The alkyl group may be, for example, a methyl group, an ethyl group, a propyl group, or an isopropyl group. 10 and R 11 The total number of carbon atoms is preferably 2 to 4, and most preferably 2.
[0038] The vinyl monomer C is usually a non-ionic vinyl monomer. Illustrative but non-limiting examples of the vinyl monomer C that can be used in the present invention include, for example, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)arylamide, N-isopropyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide or mixtures thereof (wherein "(meth)acryl" represents acryl and methacryl). Preferably, the vinyl monomer C is N,N-dimethyl(meth)acrylamide, more preferably N,N-dimethylacrylamide. The vinyl monomer C can be used alone or in combination of two or more kinds.
[0039] The content of vinyl monomer C is 20 to 75 mol %, preferably 30 to 75 mol %, more preferably 40 to 75 mol %, and most preferably 55 to 70 mol %, based on the total monomer content of the copolymer.
[0040] However, if anionic functional groups are present in the copolymer, they may prevent the formation of complexes with anionic surfactants. Thus, in a preferred embodiment, the copolymer contains a small amount of anionic functional groups (e.g., up to 10% of the total functional groups), and more preferably, the copolymer is substantially free of anionic functional groups. As used herein, "substantially free" means that the copolymer does not exhibit anionic properties at pH 3-8.
[0041] The copolymer may further comprise structural units derived from other vinyl monomers. Such other vinyl monomers include, for example, C 1-12 Esters of alcohols and (meth)acrylic acid; C 1-22 The monomer may be an amide of an alkylamine and (meth)acrylic acid, a monoester of (meth)acrylic acid with ethylene glycol, 1,3-propylene glycol, or the like, an ester having a hydroxyl group, or the above monoester etherified with methanol, ethanol, or the like, a nonionic monomer such as (meth)acryloylmorpholine, hydroxymethylacrylamide, or hydroxyethylacrylamide, an amphoteric monomer such as a betaine group-containing (meth)acrylic acid ester or a betaine group-containing (meth)acrylamide, or a semi-polar monomer such as an amine oxide group-containing (meth)acrylic acid ester or an amine oxide group-containing (meth)acrylamide. The content of such structural units derived from other vinyl monomers in the copolymer is preferably up to 30% by weight, more preferably up to 20% by weight in the copolymer.
[0042] The content of the cationic vinyl monomers A and B, the vinyl monomer C, and the constitutional units derived from other vinyl monomers in the copolymer is the amide bond moiety; 1 1 H NMR amide bond moiety or methyl group adjacent to the cationic group; or 13 It can be measured by IR absorption of C NMR.
[0043] The copolymers according to the invention preferably have a charge density of 2.0 to 4.0 milliequivalents per gram (meq / g), more preferably 2.1 to 3.5 meq / g, even more preferably 2.1 to 3.0 meq / g, and most preferably 2.5 to 3.0 meq / g. Typically, the copolymers are from 10,000 grams per mole (g / mol) to 2,000,000 g / mol, more preferably 50,000 g / mol to 1,500,000 g / mol, and most preferably 80,000 g / mol to 1,200,000 g / mol.
[0044] The copolymer of the present invention can be produced by mixing monomers of each constituent unit or their precursors, copolymerizing them by a method such as solution polymerization, suspension polymerization, or emulsion polymerization, and then subjecting them to a cationization reaction. Suitable copolymers can be prepared by known methods such as the method disclosed in EP 1911778. Examples of such copolymers include the copolymers (1 - 7) Another example is that of Mitsubishi Chemical Corporation under the trade names Diasleek C802 or TOMICIDE C-871.
[0045] Typically, the hair care compositions of the present invention contain the copolymer in an amount from 0.001 to 1% by weight of the hair care composition, more preferably from 0.01 to 0.5%, and most preferably from 0.03 to 0.3%, based on the total weight of the hair care composition, including all ranges subsumed therein.
[0046] The hair care compositions of the present invention also comprise a compound of the formula: [ka] wherein R is an alkyl or alkenyl having 8 to 18 (preferably 12 to 18) carbon atoms; M is a solubilizing cation including sodium, potassium, ammonium or mixtures thereof; and the degree of ethoxylation n is 2. Ethoxylated anionic surfactants include ethoxylated alkyl sulfate anionic surfactants having the formula:
[0047] A preferred ethoxylated alkyl sulfate anionic surfactant is sodium lauryl ether sulfate (SLES) having a degree of ethoxylation of 0.5-3, preferably 1-3, more preferably 1.5-3, and most preferably 2.
[0048] Generally, the ethoxylated alkyl sulfate anionic surfactant in the hair care compositions of the present invention will range from 0.5 to 45%, more preferably from 1 to 30%, and most preferably from 5 to 20%, based on the total weight of the hair care composition, including all ranges subsumed therein.
[0049] Typically, the hair care composition comprises the copolymer and the ethoxylated alkyl sulfate anionic active agent in a weight ratio of from 1:200 to 1:1, more preferably from 1:150 to 1:10, and most preferably from 1:100 to 1:30.
[0050] The hair care composition further comprises a zinc-based antidandruff agent, which is a compound active against dandruff, typically an antibacterial agent, preferably an antifungal agent. The zinc-based antidandruff agent is preferably water insoluble, more preferably zinc pyrithione. Zinc pyrithione (ZnPTO), an abbreviation for zinc 1-hydroxy-2-pyridinethione, is most preferred. Preferably, the zinc pyrithione is particulate having a particle size of 0.1-8 microns, more preferably 0.15-8 microns, even more preferably 0.2-5 microns, most preferably 0.25-3 microns average particle size (D50). Zinc pyrithione in the above particle sizes is available from Kolon Life Science Inc., Sino Lion (USA) Ltd, Lonza and other suppliers.
[0051] The hair care compositions of the present invention comprise a zinc-based anti-dandruff agent in an amount from 0.01 to 5%, preferably from 0.01 to 3%, more preferably from 0.05 to 2%, and most preferably from 0.05 to 1.5%, based on the total weight of the hair care composition, including all ranges subsumed therein.
[0052] Without intending to be bound by theory, the inventors believe that the combination of a copolymer having a particular structure and an ethoxylated anionic surfactant having a particular degree of ethoxylation provides controlled aggregation within a hair care product such as a shampoo, resulting in smaller aggregates of the anti-dandruff agent, ensuring uniform distribution and good retention on the scalp surface after rinsing, thus resulting in higher deposition.
[0053] The pH of the composition is preferably 4.0 or higher, and more preferably in the range of 5.0 to 7.0.
[0054] In addition to the copolymer, the hair care composition may further comprise a small amount of other cationic polymers. The other cationic polymers may be homopolymers or may be formed from two or more types of monomers. The molecular weight of the polymers is generally 5,000 to 10,000,000 g / mol, typically at least 10,000 g / mol, preferably 100,000 to 2,000,000 g / mol. The polymers will have cationic nitrogen-containing groups such as quaternary ammonium groups or protonated amino groups, or mixtures thereof.
[0055] The cationic nitrogen-containing groups are generally present as substituents on a portion of all the monomer units of the cationic polymer. The ratio of cationic to non-cationic monomer units is selected to give a polymer with a DS in the required range.
[0056] Suitable further cationic polymers include, for example, copolymers of vinyl monomers having cationic amine or quaternary ammonium functional groups with water-soluble spacer monomers such as (meth)acrylamides, alkyl and dialkyl (meth)acrylamides, alkyl (meth)acrylates, vinyl caprolactone and vinyl pyrrolidine. The alkyl and dialkyl substituted monomers preferably have C1-C7 alkyl groups, more preferably C1-3 alkyl groups. Other suitable spacers include vinyl esters, vinyl alcohol, maleic anhydride, propylene glycol and ethylene glycol. Preferably, the further cationic polymer is a cationic polysaccharide polymer, such as cationic cellulose derivatives, cationic starch derivatives and mixtures thereof.
[0057] The hair care composition may further comprise one or more cleansing surfactants in addition to the ethoxylated alkyl sulfate anionic surfactant contained in the composition. Preferably, the cleansing surfactant is an anionic surfactant.
[0058] Examples of suitable anionic cleansing surfactants are alkyl sulfates, alkaryl sulfonates, alkanoyl isethionates, alkyl succinates, alkyl sulfosuccinates, alkyl ether sulfosuccinates, N-alkyl sarcosinates, alkyl phosphates, alkyl ether phosphates, alkyl ether carboxylic acids and their salts, in particular the sodium, magnesium, ammonium, mono-, di-, triethanolamine salts. The alkyl and acyl groups generally contain 8 to 18, preferably 10 to 16, carbon atoms and may be unsaturated. The alkyl ether sulfosuccinates, alkyl ether phosphates and alkyl ether carboxylic acids and their salts may contain 1 to 20 ethylene oxide or propylene oxide units per molecule.
[0059] Exemplary anionic cleansing surfactants for use in the hair care compositions of the present invention include sodium oleyl succinate, ammonium lauryl sulfosuccinate, sodium lauryl sulfate, sodium lauryl ether sulfosuccinate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, triethanolamine dodecylbenzenesulfonate, sodium cocoyl isethionate, sodium lauryl isethionate, lauryl ether carboxylic acid, and sodium N-lauryl sarcosine.
[0060] Suitable preferred further anionic cleansing surfactants are sodium lauryl ether sulfosuccinate (n) EO (n is 1 to 3), lauryl ether carboxylic acid (n) EO (n is 10 to 20).
[0061] Mixtures of any of the foregoing anionic cleansing surfactants may also be suitable.
[0062] Generally, the total amount of additional anionic cleansing surfactant in the hair care compositions of the present invention will range from 0.5 to 45%, more preferably from 1.5 to 35%, and most preferably from 5 to 20%, based on the total weight of the hair care composition, including all ranges subsumed therein.
[0063] In particularly preferred embodiments, the hair care compositions may further comprise co-surfactants, such as amphoteric and zwitterionic surfactants, to impart mildness to the composition.
[0064] Examples of amphoteric or zwitterionic surfactants include alkylamine oxides, alkylbetaines, alkylamidopropylbetaines, alkylsulfobetaines (sultaines), alkylglycinates, alkylcarboxyglycinates, alkylamphoacetates, alkylamphopropionates, alkylamphoglycinates, alkylamidopropylhydroxysultaines, acyltaurates, and acylglutamates, the alkyl and acyl groups having 8 to 19 carbon atoms. Exemplary amphoteric and zwitterionic surfactants for use in the compositions of the present invention include laurylamine oxide, cocodimethylsulfopropylbetaine, laurylbetaine, cocamidopropylbetaine, and sodium cocoamphoacetate. Preferably, the cosurfactant is cocamidopropylbetaine (CAPB).
[0065] Typically, the co-surfactant may be present in the hair care compositions of the present invention in an amount of from 0.5 to 8% by weight of the hair care composition, preferably from 1 to 4%, based on the total weight of the hair care composition, including all ranges encompassed herein.
[0066] Hair care compositions can further comprise conditioning agents to provide conditioning effects.Typically, the most popular conditioning agents used in hair care compositions are water-insoluble oily substances such as mineral oils, naturally occurring oils such as triglycerides and silicone polymers.Conditioning benefits are achieved by the oily substances that adhere to hair forming a film, which makes hair easy to comb when wet and easy to manage when dry.Preferably, conditioning agents are non-volatile, which means that they have a vapor pressure of less than 1000 Pa at 25°C.
[0067] Preferably, the hair care composition has a mean droplet size (D) of less than 15 microns, preferably less than 10 microns, more preferably less than 5 microns, and most preferably less than 3 microns. 3,2The water-insoluble conditioning agent contains discrete dispersed droplets having an average droplet size (D 3,2 ) can be measured by laser light scattering techniques, for example, using a Malvern Instruments 2600D Particle Sizer.
[0068] The water insoluble conditioning agent may include non-silicone conditioning agents, including non-silicone oily or fatty materials such as hydrocarbon oils, fatty esters and mixtures thereof. Preferably, the water insoluble conditioning agent is an emulsified silicone oil.
[0069] Suitable silicones include polydiorganosiloxanes, especially polydimethylsiloxanes with CTFA designation dimethicone.Also suitable for use in the compositions of the present invention (especially shampoos and conditioners) are polydimethylsiloxanes with hydroxyl end groups, which have CTFA designation dimethiconol.Silicone gums with a small degree of crosslinking are also suitable for use in the compositions of the present invention, for example as described in WO 96 / 31188.Preferably, silicone oils include dimethicone, dimethiconol or mixtures thereof.
[0070] The viscosity of the emulsified silicone itself (not the emulsion or the final hair care composition) is typically at least 10,000 cSt (centistokes = mm 2 ·S -1 ), preferably at least 60,000 cSt, most preferably at least 500,000 cSt, and ideally at least 1,000,000 cSt. Preferably, the viscosity is less than 10 for ease of formulation. 9 cSt. Suitable methods for measuring the kinematic viscosity of silicone oils, such as capillary viscometers, are known to those skilled in the art. For high viscosity silicones, a constant stress rheometer can be used to measure the viscosity.
[0071] The emulsified silicone suitable for use in the hair care composition of the present invention is available as preformed silicone emulsion from silicone suppliers such as Dow Corning and GE Silicone.The use of such preformed silicone emulsion is preferred for easy processing and control of silicone particle size.Such preformed silicone emulsion typically further comprises a suitable emulsifier and can be prepared by chemical emulsification process such as emulsion polymerization or by mechanical emulsification using high shear mixer.
[0072] Examples of suitable pre-formed silicone emulsions include DC1785, DC1788, and DC7128, all available from Dow Corning, which are dimethiconol / dimethicone emulsions.
[0073] Another class of silicones that can be used are functionalized silicones, such as amino-functional silicones, which means silicones that contain at least one primary, secondary or tertiary amine group or a quaternary ammonium group. Examples of suitable amino-functional silicones include polysiloxanes with the CTFA designation "amodimethicone."
[0074] Preferably, the silicone emulsion droplets are blended with certain types of high molecular weight surface-active block polymers to form silicone emulsions, as described, for example, in WO 03 / 094874. One preferred form of surface-active block polymer having polyoxypropylene and polyoxyethylene groups as the hydrophobic and hydrophilic portions, respectively, has formula I and has the CTFA designation poloxamer, commercially available from BASF under the trade name "Pluronic".
[0075] [ka]
[0076] Suitably, the average value of x in formula I is 4 or more, preferably 8 or more, more preferably 25 or more, even more preferably 50 or more, and most preferably 80 or more. The average value of x is usually 200 or less. Suitably, the average value of y is 25 or more, preferably 35 or more, more preferably 45 or more, and most preferably 60 or more. The average value of y is usually 100 or less.
[0077] Another preferred form of surface active block polymer is according to formula II and has the CTFA designation poloxamine. They are commercially available from BASF under the trade name "Tetronic".
[0078] [ka]
[0079] The average value of a is suitably 2 or more, preferably 4 or more, more preferably 8 or more, even more preferably 25 or more, and most preferably 40 or more. The average value of a is typically 200 or less. The average value of b is suitably 6 or more, preferably 9 or more, more preferably 11 or more, and most preferably 15 or more. The average value of b is typically 50 or less.
[0080] Preferably, the surface active block polymer is a poloxamer and / or a poloxamine, more preferably the surface active block polymer is a poloxamer.
[0081] Preferably, the surface-active block polymer is blended with dimethicone, the weight ratio of dimethicone to surface-active block polymer in the blend preferably ranging from 2:1 to 200:1, more preferably from 5:1 to 50:1, even more preferably from 10:1 to 40:1, and most preferably from 15:1 to 30:1.
[0082] The water-insoluble conditioning agent is generally present in the hair care compositions of the present invention in an amount of from 0.05 to 15%, preferably from 0.1 to 10%, more preferably from 0.5 to 8%, and most preferably from 1 to 5%, based on the total weight of the hair care composition, including all ranges subsumed therein.
[0083] Preferably, the composition of the present invention further comprises a suspending agent. Suitable suspending agents are selected from polyacrylic acid, crosslinked polymers of acrylic acid, copolymers of hydrophobic monomers and acrylic acid, copolymers of carboxylic acid-containing monomers and acrylic esters, crosslinked copolymers of acrylic acid and acrylic esters, heteropolysaccharide gums and crystalline long-chain acyl derivatives. The long-chain acyl derivatives are desirably selected from ethylene glycol stearates, alkanolamides of fatty acids having 16 to 22 carbon atoms and mixtures thereof. Ethylene glycol distearate and polyethylene glycol 3 distearate are preferred long-chain acyl derivatives as they impart a pearlescent appearance to the composition. Polyacrylic acids are commercially available as Carbopol 420, Carbopol 488 or Carbopol 493. Polymers of acrylic acid crosslinked with polyfunctional agents can also be used and are commercially available as Carbopol 910, Carbopol 934, Carbopol 941 and Carbopol 980. An example of a suitable copolymer of carboxylic acid containing monomers and acrylic esters is Carbopol 1342. All Carbopol™ materials are available from Goodrich.
[0084] Suitable crosslinked polymers of acrylic acid and acrylic acid esters are Pemulen TR1 or Pemulen TR2. A suitable heteropolysaccharide gum is xanthan gum, for example available as Kelzan mu.
[0085] Mixtures of any of the above suspending agents may be used. Mixtures of crosslinked polymers of acrylic acid and crystalline long chain acyl derivatives are preferred.
[0086] The suspending agent is generally present in the hair care compositions of the present invention in an amount from 0.1 to 10%, more preferably from 0.5 to 6%, and most preferably from 0.5 to 4%, based on the total weight of the hair care composition, including all ranges subsumed therein.
[0087] The hair care compositions of the present invention may contain other ingredients common in the art to enhance physical properties and performance. Suitable ingredients include, but are not limited to, fragrances, dyes and pigments, pH adjusters, pearlizing or opacifying agents, viscosity adjusters, thickeners, preservatives, and natural hair nutrients such as botanicals, fruit extracts, sugar derivatives, and amino acids.
[0088] The compositions of the present invention are primarily intended for topical application to at least a portion of an individual's scalp and / or hair in a rinse-off or leave-on composition, preferably a rinse-off composition such as a shampoo.
[0089] The following examples are provided to facilitate understanding of the present invention and are not provided to limit the scope of the claims.
[0090] Working Example Example 1 This example illustrates the flocculation profile of a shampoo composition. The composition was prepared according to the formula detailed in Table 1. All ingredients are expressed as weight percent of the total formulation and as the concentration of the active ingredient.
[0091] [Table 1]
[0092] a. A commercially available copolymer is available from Mitsubishi Chemical Corporation under the trade name Diasleek C802 and has a charge density of 2.3 meq / g. b. Guar hydroxypropyltrimonium chloride is commercially available from Ashland under the trade name BF13, having a charge density of 0.67 meq / g to 0.86 meq / g and a molecular weight of 1,000,000 to 1,500,000 g / mol. c. Commercially available dimethicone pre-blended with Dow corning poloxamer with particle size of 10 μm. d. Commercially available dimethiconol from Dow corning with particle size of 0.2 μm.
[0093] method 1 g of test shampoo sample was diluted with 9 g of water in a centrifuge tube. The tube was then shaken on a vortex mixer for 30 seconds. Three replicates of each shampoo were prepared simultaneously.
[0094] The dilutions were immediately imaged under a microscope. 20 μg of the diluted sample was placed on a glass microscope slide with a cover slip on top. An Olympus BX51 microscope was used at 10x magnification. Three images were taken of different areas for each replicate.
[0095] The freshly prepared dilutions were added to the sample cells and the aggregate particle size distribution was measured using a Malvern Master.
[0096] result It can be seen from the aggregate particle size distribution graph (Figure 1) that sample 1 containing the copolymer showed a much smaller aggregate size than sample 2 containing the guar polymer. The aggregate particle size of sample 1 was located in the range of 0.1-1 μm.
[0097] The microscopic images also showed that sample 1 formed smaller aggregate sizes than sample 2.
[0098] Example 2 This example demonstrates the effect of the degree of ethoxylation of anionic surfactants on the flocculation profile of a shampoo composition. All ingredients are listed as weight percent of the total formulation and as the concentration of the active ingredient.
[0099] [Table 2]
[0100] e. A commercially available copolymer is available from Mitsubishi Chemical Corporation under the trade name TOMICIDE C-871 and has a charge density of 2.63-2.73 meq / g.
[0101] method The same protocol as described in Example 1 was used to assess aggregate particle size.
[0102] result Both the microscopic images (Figure 2) and the aggregate size distribution graph (Figure 3) showed that sample 3 containing SLES(2EO) formed smaller aggregate sizes than sample 4 containing SLES(3EO).
Claims
1. the below described: a) copolymer; b) Formula: 【Chemistry 1】 where R is an alkyl or alkenyl having 8 to 18 carbon atoms; M is a solubilizing cation comprising sodium, potassium, ammonium or mixtures thereof; The degree of ethoxylation n is 2. an ethoxylated alkyl sulfate anionic surfactant having the formula: c) 0.01 to 5% by weight of a zinc-based anti-dandruff agent A hair care composition comprising: The copolymer may be: (i) Formula (1): 【Chemistry 2】 (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 ~R 4 Each of the above may be independently selected from the group consisting of C 1-24 is an alkyl group, and X - are independently a fluoride, chloride, bromide, or iodide anion, and d is an integer from 1 to 10. A cationic vinyl monomer A represented by: (ii) Formula (2): 【Chemistry 3】 (In the formula, R 5 is a hydrogen atom or a methyl group, R 6 ~R 8 Each of the above may be independently selected from the group consisting of C 1-24 is an alkyl group, - are independently a fluoride, chloride, bromide, or iodide anion, and e is an integer from 1 to 10. a cationic vinyl monomer B represented by (iii) Formula (3): 【Chemistry 4】 (In the formula, R 9 is a hydrogen atom or a methyl group, R 10 and R 11 Each of the groups independently represents a hydrogen atom or C 1-4 is an alkyl group, where R 10 and R 11 The total number of carbon atoms is 1 to 4. Vinyl monomer C represented by Including, the content of monomer A is 1-44 mol %, based on the total monomer content of the copolymer; the content of monomer B is 1-44 mol %, based on the total monomer content of the copolymer; A hair care composition, wherein the content of monomer C is 20-75 mol % based on the total monomer content of the copolymer.
2. In the formula (1), R 2 ~R 4 Each of the above is independently C 1-3 The hair care composition of claim 1 , wherein the alkyl group is an alkyl group.
3. In the formula (1), X - The hair care composition of claim 1 or 2, wherein:
4. In the formula (2), R 6 ~R 8 Each of the above is independently C 1-3 The hair care composition according to any one of claims 1 to 3, wherein the group is an alkyl group.
5. In the formula (2), Y - The hair care composition of any one of claims 1 to 4, wherein:
6. A hair care composition according to any preceding claim, wherein the ethoxylated alkyl sulfate anionic surfactant is sodium lauryl ether sulfate.
7. R of the monomer A 1 is a hydrogen atom, R 2 ~R 4 Each of these is C 1-3 The hair care composition according to any one of claims 1 to 6, wherein the group is an alkyl group.
8. A hair care composition according to any one of claims 1 to 7, wherein the monomer A is acryloylaminopropyl-N,N,N-trimethylammonium chloride.
9. R of the monomer B 5 is a methyl group, R 6 ~R 8 Each of these is C 1-3 The hair care composition according to any one of claims 1 to 8, wherein the group is an alkyl group.
10. 10. The hair care composition according to any one of claims 1 to 9, wherein the monomer B is N-methacryloyloxyethyl-N,N,N-trimethylammonium chloride.
11. R of the monomer C 9 is a hydrogen atom, R 10 and R 11 Each of these is C 1-3 The hair care composition according to any one of claims 1 to 10, wherein the group is an alkyl group.
12. A hair care composition according to any one of claims 1 to 11, wherein the monomer C is N,N-dimethylacrylamide.
13. A hair care composition according to any one of the preceding claims, wherein the cationic charge density of the copolymer is from 2.0 to 4.0 meq / g.
14. 14. The hair care composition of claim 13, wherein the copolymer has a cationic charge density of from 2.1 to 3.5 meq / g.
15. A hair care composition according to any one of the preceding claims, wherein the molecular weight of the copolymer is from 10,000 g / mol to 2,000,000 g / mol.
16. 16. The hair care composition of claim 15, wherein the molecular weight of the copolymer is from 50,000 g / mol to 1,500,000 g / mol.
17. 17. The hair care composition of claim 16, wherein the molecular weight of the copolymer is from 80,000 g / mol to 1,200,000 g / mol.
18. A hair care composition according to any one of the preceding claims, comprising said copolymer in an amount of 0.001 to 1%.
19. 19. A hair care composition according to claim 18 comprising said copolymer in an amount of 0.01 to 0.5%.
20. A hair care composition according to any one of the preceding claims, comprising said copolymer and said ethoxylated alkyl sulphate anionic surfactant in a weight ratio of from 1:200 to 1:
1.
21. 21. The hair care composition of claim 20 comprising said copolymer and said ethoxylated alkyl sulfate anionic surfactant in a weight ratio of from 1:150 to 1:
10.
22. A hair care composition according to any preceding claim, wherein the zinc-based anti-dandruff agent is zinc pyrithione.
23. 23. A method of depositing an anti-dandruff agent on the scalp, comprising the steps of applying a composition according to any one of claims 1 to 22 to the scalp surface of an individual, and thereafter rinsing said surface with water.
Citation Information
Patent Citations
Washing composition
JP1983196300A
scalp treatment
JP2006516022A
Cosmetic composition and hair wash
JP2010215619A